2021
DOI: 10.1021/acssuschemeng.1c05538
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Defects Activating Fe-Doped Molybdenum Sulfide@N-Doped Carbon Heterostructures for Efficient Electrochemical Hydrogen Evolution

Abstract: Vacancy defects caused by doping are beneficial to optimizing the regional electronic structure and increasing exposed active sites, and it is vital to improve the efficiency of hydrogen evolution reaction (HER). Herein, we constructed the Fe-doped molybdenum sulfide encapsulated with N-doped carbon (FeMoSN@ NC), which with ultrathin edge-curled layer structure. Fe-doping realized with Prussian blue nanocages as the precursors, which plays a crucial role in the formation of ultrathin layer assembled microspher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…For instance, Xia et al constructed a Fe‐doped molybdenum sulfide (MoS 2 )@N‐doped carbon heterostructure (FeMoS@NC). [ 165 ] The Fe‐doping in MoS 2 can introduce high‐density vacancies, thus promoting the activity of the electrode material. To investigate the improved performance of FeMoSN@NC, the author carried out the DFT calculation to study the adsorption energy.…”
Section: Strategies To Incorporate the Defects Into The Hetero‐interfacementioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Xia et al constructed a Fe‐doped molybdenum sulfide (MoS 2 )@N‐doped carbon heterostructure (FeMoS@NC). [ 165 ] The Fe‐doping in MoS 2 can introduce high‐density vacancies, thus promoting the activity of the electrode material. To investigate the improved performance of FeMoSN@NC, the author carried out the DFT calculation to study the adsorption energy.…”
Section: Strategies To Incorporate the Defects Into The Hetero‐interfacementioning
confidence: 99%
“…The elemental doping method can not only regulate the energy band and electronic structure, but also allow the formation of chemical bonds through the doped atoms at the hetero‐interfaces, promoting the charge transfer and reducing the volume expansion during the electrochemical reaction. [ 165,166 ] Ren et al synthesized a heterostructure formed by hybridized vanadium oxide (VO/V 2 O 3 ) and N‐doped carbon (NC) as an anode material for sodium‐ion batteries. [ 166 ] The authors analyzed the optimized geometry of the heterostructure and showed that the N doping can significantly increase the affinity of graphene for Na ions and VO.…”
Section: Strategies To Incorporate the Defects Into The Hetero‐interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Interface engineering as an effective method could improve the catalytic performance. , By optimizing the electronic structure of cobalt selenide, the design of multicomponent hybrid electrocatalysts (e.g., CoSe 2 @CoNi LDH and CoSe 2 /CoP) could accelerate the reaction rate of the Volmer step, and then, the catalytic process of cobalt selenide could be optimized. ,, Although numerous electrocatalysts on interface engineering have been reported, there are few reports on designing an effective cobalt selenide-based electrocatalyst via compatible heterojunction fabrication. Actually, good interfacial compatibility is very important for improving the strength and density of interfacial bonding, which would significantly affect the catalytic activity and stability of electrocatalysts, but it is often neglected in the design of efficient electrocatalysts with an abundant heterointerface .…”
Section: Introductionmentioning
confidence: 99%
“…However, the precious metal catalysts are scarce and expensive. Therefore, more and more researchers have tried to develop many non-precious-metal-based electrocatalysts, including metal/alloy, , oxide, hydroxide, layered double metal, sulfide, phosphide, phosphate/borate, , boride, nitrite, , and other compounds. However, the electrochemistry capability of the majority of these catalysts is still not as good as that of precious metal.…”
Section: Introductionmentioning
confidence: 99%